Ekstraksi lead crt ventrikel kiri yang patah - Isyana Miranti; Made Satria Yudha Dewangga; Widyo Mahargo; Sulistiyati Bayu Utami; yoga Yuniadi (The Indonesian Heart Association, 2015)
In recent years, implantation of cardiac resynchronization therapy (CRT) devices has significantly increased. Left ventricular (LV) pacing through the Coronary Sinus (CS) is the standard approach for CRT. Many LV lead placement techniques to get lead stability and optimal threshold, one with wire PCI. We presented a case with LV lead CRT extraction were broken after being fitted with wire PCI with stabilization purpose and to obtain an appropriate threshold, the extraction was done by snaring techniques.